Inhibition test of the pirdot leaf (saurauia vulcani korth) extract to the growth of streptococcus mutans bacteria in oral cavity with in vitro - Gostry A. Dohude; Noviyanti (Journal of Dentomaxillofacial Science, 2021)
Objective: This study aims to determine effectiveness of pirdot leaf (Saurauia vulcani Korth) extract as an antibacterial against the growth of Streptococcus mutans bacteria. Material and Methods: The study is experimental laboratories with post-test only control group design. The study sample use Streptococcus mutans bacteria that multiply and cultivation in Microbiology Laboratory of the Pharmacy Faculty, Universitas Sumatera Utara. Pirdot leaves that used for this research is collected from Sipangan Bolon village, Girsang regency, North Sumatera, Indonesia and extracted at the Laboratory of Traditional Medicine at the Faculty Pharmacy in Universitas Sumatera Utara. This research use six treatment group concentration of 50%, 25%, 12,5%, 6,25% from pirdot leaves extract, Amoxicillin (positive control), and Aquadest (negative control). The testing in six treatment group for the Streptococcus mutans bacteria are using diffusion method namely Kirby-Bauer with four repetition. The production to get extraction of pirdot leaf used maceration method and using 70% ethanol as a solvent. Results : This research indicate that Pirdot (Saurauia vulcani Korth) leaf can inhibit growth of Streptococcus mutans bacteria that can be seen from clear zone at paper discs that have been given Pirdot leaves extract with 50%, 25%, 12,5%, 6,25% concentration, Amoxicillin (positive control), and Aquadest (negative control). The results also showed a significant difference from diameter of the inhibition zone at each treatment group (p<0,005). Conclusion: Pirdot leaf extract has antibacterial effect that can inhibit the growth of Streptococcus mutans in oral cavity with in vitro. At a concentration of 50% is more effective to inhibit the growth of Streptococcus mutans in oral cavity with in vitro.